A Representation of SDGs: Payments for Forest Environmental Services (PFES) in Loc Tien Commune, Phu Loc District, Thua Thien Hue Province - Mai Thi Khanh Van (Jurnal Sentris, 2020)
In Vietnam, the policy on payment for forest environmental services (PFES) has been present for a long time, in the orientation of socialization of national forest protection. The role of this policy was not limited to the objective of environmental protection, the overarching objective of PFES has always been the link to develop the sector of environment, economy, and society. This has also been one of the targets of Goal 11: "Sustainable Cities and Communities" within the 17 Sustainable Development Goals (SDGs), set out by the United Nations. At the study site is Loc Tien commune, in Phu Loc district, Thua Thien Hue province, by in-depth interviews with local people and officials, the implementation of PFES, and its ability to meet the targets in Goal 11 were clarified. The PFES implementation mechanism has been well-established with the full range of stakeholders and their specific roles. However, the gained efficiency from PFES has not met the Vietnamese Government's goals that were to support positive economic, social, and environmental links. The aim to protect the forest environment has been implemented, however, the livelihoods and income of local communities have not improved visibly. In the future, to address current issues, policymakers should consider more solutions to advance the local livelihoods.